Nuancing Interdisciplinarity: Between and Beyond Liberal Arts and Professional Education - Trinidad, Jose Eos R (Archīum Ateneo, 2021)
In an environment of ever-increasing cost of higher education and a precarious economic market, students and families labor over the right “major.” Although many opt for technical and professional training, not a few still advocate for a liberal arts education. In this essay, I argue that interdisciplinarity—or the integration of two or more disciplines—can be present in both liberal arts and professional education although they have differing aims, bases, and means, depending on the general field. Interdisciplinarity in the liberal arts highlights humanistic questions, broad thinking, and understanding the whole. In technical professional education, it emphasizes practical problems, deep thinking, and understanding complexities. Highlighting these differences, however, is done not to separate them but to bridge them and lead to greater appreciation of the unique contribution of an interdisciplinary perspective on both fields of learning. Examples from a Philippine university are used to ground these ideas of distinguishing and connecting interdisciplinarity in liberal arts and professional education.